Sutureless superficial anterior lamellar keratoplasty for recurrent corneal haze after repeat excimer laser surface ablation. Issue 3 (5th July 2019) - Myerscough, James; Bovone, Cristina; Thomas, Peter Benjamin Michael; Mimouni, Michael; Aljassar, Faisal; Padroni, Sara; Busin, Massimo
Abstract : Background/Aims: To evaluate the 5-year outcomes of sutureless superficial anterior lamellar keratoplasty (SALK) in the treatment of surface ablation-related corneal haze recurring after phototherapeutic keratectomy (PTK). Methods: Prospective interventional study at a tertiary referral centre in Forli, Italy. Ten consecutive eyes with corneal haze following photorefractive keratectomy, recurring after treatment with PTK with or without mitomycin C, undergoing sutureless SALK. Sutureless SALK was performed using a microkeratome in donor and recipient. Main outcome measures: best spectacle-corrected visual acuity (BSCVA), surgically induced astigmatism (SIA), rate of recurrence and complications. Results: There were no intraoperative complications and there was no recurrence of haze in any eye postoperatively. BSCVA showed significant improvement at all postoperative time points. Mean preoperative visual acuity improved from 0.46 logMAR units (SD=0.12) to 0.12 (SD=0.12, p=0.0001) at 5 years. At 6 months, SIA was 2.50±1.04 with no further significant change at 5 years (2.53±1.39, p=0.95). There was no significant change in mean spherical equivalent and no significant difference between preoperative and postoperative astigmatism vector values at 5 years. Conclusions: Sutureless SALK provides a useful treatment option in patients with recurrent haze after excimer laser treatment. It can eliminate haze recurrence for at least a period of 5 years and can improve BSCVA, although there may be significant SIA.